MANGROVE COVERAGE CHANGE DETECTION USING LANDSAT IMAGERIES BASED ON HYBRID CLASSIFICATION IN KEMBUNG RIVER, BENGKALIS ISLAND, RIAU PROVINCE - Romie Jhonnerie; Vincentius P Siregar; Bisman Nababan; Lilik Budi Prasetyo; Sam Wouthuyzen (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2014)
ABSTRACT The limited scientific information and lack of attention from stakeholders on the status of mangroves in Kembung River functioned as a basis of this study. Four series of Landsat data recorded in 1996, 2002, 2010, and 2013 were used to map mangrove land cover and changes detection. Hybrid classification technique, a combination of the object-based and random forest classifications, were applied in this study. The result showed that based on hybrid classification, mangrove coverage was detected within 82.6-88.4% overall accuracy. Change detection analyses showed that the mangrove area of Kembung River was relatively stable. For nearly two decades, we found mangrove loss about 197.2 ha, gain of 251.1 ha, and unchanged of 2904.9 ha. Changes in mangrove were generally caused by anthropogenic factors such as mangrove replanting, logging, changes over the function of mangroves into the road, embankment, settlement, shrimp farms, and natural growth. Serious attention from various parties are needed to maintain the existence and sustainablility of mangrove ecosystems in Kembung River.   Keywords: Mangrove, Sungai Kembung, monitoring, Landsat, hybrid classification